A REVIEW OF THE COMMON PARASITES AND DISEASES OF FISH IN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
The aquaculture sector in Nigeria has witnessed significant growth over the past few decades, contributing to food security and economic development. However, this growth has been accompanied by challenges, particularly concerning fish health. Fish parasites and diseases are significant constraints to aquaculture and wild fisheries in Nigeria, impacting food security, economic growth, and biodiversity. This review synthesizes current knowledge on the prevalence, distribution, and impact of common parasites and diseases affecting fish in Nigeria. The findings reveal the need for improved surveillance, diagnostics, and management strategies to mitigate the impact of these pathogens on Nigeria’s fisheries sector. Further research is required to explore the zoonotic potential of some parasites and their implications for public health.
Keywords: Nigeria; Review; Parasites; Diseases; Fish